PERLINDUNGAN HUKUM TERHADAP DEBITUR (PELAKSANA PEKERJAAN) DALAM PELAKSANAAN PERJANJIAN UPAH BORONG (PARTISIPATIF) DALAM PROYEK SWAKELOLA DI LINGKUNGAN PEKERJAAN UMUM KABUPATEN DELI SERDANG - Taufik Hasudungan Sihotang; Ningrum Natasya Sirait; Tan Kamello; Mahmul Siregar (Universitas Sumatera Utara, 2017)
ABSTRACT Government procurement of goods and service is a very essential part in the process of implementing the development. Without adequate equipment and infrastructure, the implementation of government’s work will be disturbed and it will not achieve the maximum results. In order to achieve such results, comprehensible legal regulations are required, especially regarding rights and obligations of parties that execute the work. It is closely related to the agreement made in the implementation of contracted works as stipulated in Article 1601 b of the Civil Code. According to the agreement, the work results can be accounted for in terms of its physic, finance, and usefulness for the uninterrupted flow of government work and service. The thesis discusses some problems, namely how the protection for debtor (work executor) is in the agreement to the contracted work wages (participating) in self management project at the public works of Deli Serdang Regency and how the protection for debtor (work executor) is in the implementation of the agreement to the contracted work wages (participating) in the self management project at the public works of Deli Serdang Regency. The thesis uses analytical prescriptive judicial normative research method. It used the theory of Legal Protection. The data were gathered by using primary, secondary, and tertiary legal materials, supported by approach methods, namely statute approach, conceptual approach and case approach. The gathered data were analyzed qualityatively. The results showed that: First, in the agreement to the contracted work wages between the debtor (private party/contractor) and the creditor (government /employer), the debtor had weaker position compared to the creditor. The debtor is vulnerable to endure loss that was uncertainly paid by the creditor. Secondly, the agreement to the contracted work wages did not reflect balance principle in which the debtor bear their own obligations, for which in this research the debtor took legal action to obtain legal protection, so that the agreement world reflect the balance principle. Keywords: Legal Protection, Debtor (Work Executor), Self Management